Glutamate cycle changes in the putamen of patients with de novo Parkinson's disease using 1H MRS. (June 2022) - Chassain, Carine; Cladiere, Aurélie; Tsoutsos, Camille; Pereira, Bruno; Boumezbeur, Fawzi; Debilly, Bérangère; Marques, Ana-Raquel; Thobois, Stéphane; Durif, Franck
Abstract: Introduction: To investigate glutamatergic metabolism changes in the putamen of patients with de novo Parkinson's Disease (PD) and test the hypothesis that glutamate (Glu) levels are abnormally elevated in the putamen contralateral to where the motor clinical signs predominate as expected from observations in animal models. Methods: 1 H NMR spectra from 17 healthy control volunteers were compared with spectra from 17 de novo PD patients of who 14 were evaluated again after 2–3 years of disease progression. Statistical analysis used random-effects models. Results: The only significant difference between PD patients and controls was a higher glutamine (Gln) concentration in the putamen ipsilateral to the hemibody with predominant motor signs (Visit 1: 6.0 ± 0.4 mM vs. 5.2 ± 0.2 mM, p < 0.05; Visit 2: 6.2 ± 0.3 mM vs. 5.2 ± 0.2 mM, p < 0.05). At Visit 1, PD patients had higher Glu and Gln levels in the putamen ipsilateral versus contralateral to dominant clinical signs (Glu: 12.2 ± 0.6 mM vs. 10.4 ± 0.6 mM, p < 0.05; Gln: 6.0 ± 0.4 mM vs. 4.8 ± 0.4 mM, p < 0.05; Glu and Gln pool (Glx): 17.9 ± 0.8 mM vs. 14.7 ± 1.1 mM, p < 0.05). At Visit 2, the sum of the two metabolites remained significantly higher in the ipsilateral versus contralateral putamen (Glx: 18.3 ± 0.6 mM vs. 16.1 ± 0.9 mM, p < 0.05). Conclusion: In de novo PD patients, the putamen ipsilateral to the more affected hemibody showed elevated Gln versus controls and elevated Glu and Gln concentrations versus the contralateral side. Abnormalities in Glu metabolism therefore occur early in PD but unexpectedly in the putamen contralateral to the more damaged hemisphere, suggesting they are not dependent solely on dopamine loss. Highlights: MRS assesses glutamate, glutamine levels from the putamen of de novo parkinsonian patients. Glutamate, glutamine levels are higher in the putamen ipsilateral to clinical signs. Abnormalities in Glutamate metabolism therefore occur early in Parkinson Disease. However, changes occur unexpectedly in the putamen of the less damaged hemisphere. Metabolic changes are not dependent solely on dopamine loss.